If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + 2(6Y) = 126 Remove parenthesis around (6Y) 2X + 2 * 6Y = 126 Multiply 2 * 6 2X + 12Y = 126 Solving 2X + 12Y = 126 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-12Y' to each side of the equation. 2X + 12Y + -12Y = 126 + -12Y Combine like terms: 12Y + -12Y = 0 2X + 0 = 126 + -12Y 2X = 126 + -12Y Divide each side by '2'. X = 63 + -6Y Simplifying X = 63 + -6Y
| 0.4t=0.7+0.6t | | 5(4x-8)=-20 | | -2(3x+5)+4-7x=6x-18 | | (3P-4)=-25 | | 2.5x=100-2.5x | | 34five+23five= | | 15+9u-3=16+-2u-7 | | 4a^2-11a=3 | | -2/3w-8/15=-4/5 | | 15+9u-3=16-2u-7 | | tan^2x=0.25 | | 3y-27=-15 | | 13/48+x/2-(2x+1)/6=1 | | h=-16t^2+44t+7 | | 6+-2=y | | (x+14)(x+3)=0 | | -4k+2(5k-6)=-3k-30 | | -4(2x+4)=12x-8 | | 4x=6x-3 | | 3x+2x=85 | | 20-18=200 | | .003x-.2=.01 | | 15p+9-11-p=-2(2p+4)-3(2p-2) | | -4(7-2t)=4(t-1) | | 3y*2+3(4y*2-2)= | | y^2+10y=11 | | -5x-6(2x-2)=-107 | | -8(3x+12)-13=4x+10 | | 2x+9=4(x+6) | | 15x+11x+20=90 | | 5x-10=-7x-70 | | y-19=6 |